SUMBANGAN DIMENSI KUALITAS JASA KEPADA KEPUASAN DAN LOYALITAS KONSUMEN PADA PO. WAHYU DI SUKOHARJO - Marsudi, Hidup; Nalurita, Wening (Surakarta Management Journal, 2024)
Aspects of the quality of services provided by PO. Revelation as one of the main elements of improvement in service quality is indeed appropriate to be evaluated, so that it is known how far service quality has been achieved, what efforts must be made to achieve excellent quality, and consumers feel satisfaction in enjoying the services provided, In the end they make repeat purchases and become loyal customers. Formulation of the problem in this research: 1) Do the service quality dimensions consisting of tangible, reliability, responsiveness, assurance, and empathy contribute to consumer satisfaction and loyalty, either partially or jointly?; 2) Does satisfaction contribute to consumer loyalty?; 3) Which dimensional factors of service quality make the greatest contribution to consumer satisfaction and loyalty? The objectives of this research: 1) To determine the contribution of service quality dimensions consisting of tangible, reliability, responsiveness, assurance, and empathy to consumer satisfaction and loyalty both partially and jointly; 2) To determine the contribution of ownership satisfaction to consumer loyalty; 3) To find out the dimensional factors of service quality that make the greatest contribution to consumer satisfaction and loyalty. The hypotheses proposed are: 1) There is a contribution of service quality dimensions consisting of tangible, reliability, responsiveness, assurance, and empathy to consumer satisfaction and loyalty both partially and jointly; 2) There is a contribution of consumer satisfaction to consumer loyalty; 3) The service quality dimension factor that makes the greatest contribution to consumer satisfaction and loyalty is the reliability factor. The analytical tools used in the research are: Validity test, reliability test, moderated regression analysis, coefficient of determination, t test and F test. Based on the results of the analysis, it can be concluded: 1) There is a contribution of service quality dimensions consisting of tangible, reliability, responsiveness, assurance and empathy to consumer satisfaction and loyalty both partially and jointly; 2) There is a contribution of consumer satisfaction to consumer loyalty; and 3) The service quality dimension factor that makes the greatest contribution to consumer satisfaction and loyalty is the reliability factor.